The Analysis of the Disharmonization of Institutional Authority in Regional Financial Oversight - Dhea Nisa Arinanda; Muh. Ali Masnun; Alfiani Dwiyani (Indonesian Journal of Administrative Law and Local Government, 2025)
This study aims to analyze the disharmonization of institutional authority in regional financial supervision and its implications for the effectiveness of oversight mechanisms. In many regional governance systems, financial supervision is carried out by multiple institutions with different legal bases, mandates, and scopes of authority. However, the absence of clear coordination frameworks and the overlap of institutional functions often create disharmony in the exercise of supervisory authority. This research focuses on identifying the forms and causes of such disharmonization, particularly in relation to overlapping mandates, unclear division of responsibilities, and inconsistencies in regulatory arrangements governing regional financial supervision. Using a normative and analytical approach, this study examines relevant laws, regulations, and institutional practices that shape the structure of regional financial oversight. The findings indicate that institutional disharmonization leads to fragmented supervision, duplication of control functions, and gaps in monitoring processes, which ultimately weaken the effectiveness of regional financial supervision. In addition, disharmonized authority tends to create uncertainty among supervisory institutions, reduce institutional accountability, and limit the ability of oversight bodies to respond effectively to financial irregularities. This condition also undermines the consistency of supervisory standards and weakens the overall integrity of the regional financial management system. The study concludes that institutional harmonization is essential to strengthen regional financial supervision, requiring clearer legal frameworks, precise delineation of authority, and improved coordination among supervisory institutions. Addressing institutional disharmonization is therefore a key prerequisite for enhancing the effectiveness and coherence of regional financial oversight. Keywords: Disharmonization, Authority, Oversight, Governance, Regional Finance